Coefficient estimates and subordination properties for certain classes of analytic functions of reciprocal order - Al-HAWARY, Tariq; FRASIN, Basem Aref (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this work, we determine the coefficient bounds and subordination results for functions in certain subclasses of analytic functions of reciprocal order, which are introduced here by means of a Hadamard product of analytic functions. The results presented in this paper improve or generalize the recent works of other authors and also give rise to several new results. Mathematics Subject Classification (2010): 30C45, 30C80.